Analisis Pemberdayaan Perempuan Dalam Ekonomi Politik Terhadap IPM Perempuan di Indonesia Tahun 2015-2023 - Rika Kurnia; Any Eliza; Okta Supriyaningsih (CV. Ulil Albab Corp, 2025)
The low HDI of women in Indonesia causes gender inequality. The purpose of this study is to examine women's empowerment in the political economy on women's HDI in Indonesia from 2015 to 2023. This type of research uses a quantitative type. The secondary data used in this analysis comes from the official website of the Indonesian Central Bureau of Statistics (BPS), and the technique used is panel data regression which is then processed using the E-views 10 application with the panel data regression method and the Fixed Effect Model is determined as the most optimal model for analyzing the effect of independent variables on the dependent variable partially or simultaneously. The results stated that partially, the variable percentage of women entrepreneurs had a negative and insignificant effect on the HDI of women in Indonesia, the variable percentage of women as managers, professionals, administrators and technicians had a positive and significant effect on the HDI of women in Indonesia, while the variable of women in parliament had a significant negative effect on the HDI of women in Indonesia. The results of the analysis simultaneously variable percentage of women entrepreneurs, percentage of women as managers, professionals, administrators, and technicians, percentage of women in parliament have a significant effect on the HDI of women in Indonesia in 2015-2023.